2020
DOI: 10.1037/spq0000420
|View full text |Cite
|
Sign up to set email alerts
|

History of the future of proactive school psychology: Historical review at our 75th APA anniversary to transcend the past, excel in the present, and transform the future.

Abstract: The purpose of this article was to historically review the field of school psychology for the 75th Anniversary of the founding of the Division of School Psychology (DSP) of the APA. Past and present proactive school psychology was evaluated and recommendations for the future were offered in light of historic APA DSP goals. Since its inception, the DSP has worked with APA to protect and expand school psychology as a foundational service area within health service psychology. This article examines the challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…We strongly recommend that school psychology professionals commit to the social justice action in the School Psychology Unified Antiracism Statement and Call to Action (Garcia-Vazquez et al, 2020) to eradicate racism and educational disparities; ensure that culturally adapted, evidence-based comprehensive services are equitability accessible to all students with needs (Hughes et al, 2020; Nastasi et al, 2020); and rejuvenate programs of research to consider the ecology, physiology, psychology, and culture of each student (Jimersen et al, 2020; Klingball et al, 2020; Kranzler et al, 2020). More critically, it is all D16 members (not only the executive board) who are critical to the vitality of the division, the success of APA, and the field of school psychology (D’Amato et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We strongly recommend that school psychology professionals commit to the social justice action in the School Psychology Unified Antiracism Statement and Call to Action (Garcia-Vazquez et al, 2020) to eradicate racism and educational disparities; ensure that culturally adapted, evidence-based comprehensive services are equitability accessible to all students with needs (Hughes et al, 2020; Nastasi et al, 2020); and rejuvenate programs of research to consider the ecology, physiology, psychology, and culture of each student (Jimersen et al, 2020; Klingball et al, 2020; Kranzler et al, 2020). More critically, it is all D16 members (not only the executive board) who are critical to the vitality of the division, the success of APA, and the field of school psychology (D’Amato et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To lay the foundation. D’Amato and Perfect (2020) provided an integrated overview of historical influences in school psychology governance, training, research, and practice. These historical figures and events surface in some of the other articles in the Special Issue to demonstrate connections with each domain.…”
Section: Understanding and Integrating The Past Present And Futurementioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars contend that school psychology trainers have generally been slow adopters of computer-based training technologies (Bocanegra & Gallup, 2019). Nevertheless, scholars have recently noted the role that technologies (e.g., distance learning) may play in helping overcome some of the field's biggest challenges, such as ending the shortages crisis (Bocanegra & Gallup, 2019;D'Amato & Perfect, 2020). Research into the proliferation of online instruction in higher education, surveying only pre-pandemic usage, found that the use of distance education had increased for the 14th year in a row and had been growing faster than previous years with 31.6% of all students taking at least one distance course (Seaman et al, 2018).…”
Section: Technology-mediated Instructionmentioning
confidence: 99%